SKI AREAS AND SLOPES IN ROMANIA. REVIEWING CURRENT STATE OF WINTER SPORTS TOURISM UNFOLDING POSSIBILITIES WITHIN CARPATHIAN MOUNTAINS - N. CIANGĂ; BIANCA SORINA RĂCĂŞAN (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
Ski Areas and Slopes in Romania. Reviewing Current State of Winter Sports Tourism Unfolding Possibilities within Carpathian Mountains. This study is reviewing nowadays Romania’s tourism supply (2015) – laying special emphasis on the North-West Development Region’s situation – in terms of winter sports potential (resources) and material and technical base (specific infrastructure). It calls into question a highly discussed topic within the domain of interest of Tourism Geography, whose recursiveness could be justified by countinuous changes that influence the quantitative and qualitative configuration of ski areas, ski tracks and related equipment2. The existence of favourable natural support in terms of relief and climate is an indispensable prerequisite to the development of winter sports tourism within any area. From this point of view, the presence of the Carpathians is a major advantage for Romania, the more so as the proportion of the mountain sector represents 30 percent of the national area (238,391 square kilometres). By occupying different amounts of the territory belonging to 6 development regions and 19 counties, heterogeneous tourism potential values have emerged, causing unequal exploitation opportunities within the mountain area. The purpose of this paper is to provide a general framework of Romanian ski slopes, areas and corresponding facilities for assessing their current state, from regional perspective, with emphasis on North-West’s situation. On this line, the main objectives, starting from identifying and inventorising to classifying regions and ski tracks based on hierarchical categories, also deal with ranking slopes according to surface, length, width, elevation of departure point, difference in elevation, difficulty ratings, capacities of slopes and cable transportation means. In order to achieve these goals, quantitative research methods and techniques mostly refered to observation, analysis, synthesis and comparison of statistical data, well-synthesized within tables, graphical and cartographical representations. Aiming to highlight Romania’s specificity concerning mountain tourism and winter sports unfolding possibilities, with an almost century-old tradition, came out that the best numerical and typological tourism supply representation belongs to the Central Region whereas for the North-West Development Region, Maramureş and Cluj counties impose themselves through the potential of their largest ski areas and resorts: Cavnic and Muntele Băişorii.